Dyke-Davidoff-Masson syndrome as sequelae of typhoid encephalitis? - Agarwal, Sheetal; Yadav, Dinesh Kumar; Beniwal, Mukesh Kumar; Singh, Archana (Indian Journal of Child Health, 2014)
Dyke-Davidoff-Masson syndrome (DDMS) is characterized by cerebral hemiatrophy with homolateral hypertrophy of the skull and sinuses in association with contralateral hemiplegia, seizures, mental retardation, difficulty, and impairment of speech development. Among the various complications of typhoid fever, neuropsychiatric manifestations constitute a major portion. However, DDMS post typhoid encephalitis has not been reported in the literature. We report a case of DDMS in an 8-year-old boy who presented with multiple seizures, impaired speech, behavioral changes, and mental retardation following typhoid encephalitis.